Improving Learning Experience of People with Cognitive Disabilities Using Serious Games: A Review - Chakraborty, Anirban; Ojo, Eseohen; Quonoey, Bryce; Mehta, Gayatri (European Scientific Journal, ESJ, 2021)
Serious games have grown as one of the alternative means to assist people with cognitive and learning disabilities. They have been found to have a positive influence on these people and to help them improve their social skills. They offer them a stress-free environment that assists them in working on their skills at their own pace. Studies have shown that no one game is fit for all kinds of disabilities. Instead, these games must be tailored according to the specific needs of the disability. This paper discusses some of the prevalent serious games and the frameworks that can be used while designing them. Serious games need to be made broadly accessible for people in developing countries to increase their efficacy. Using serious games has helped the disabled to overcome their anxiety, as well as help them in coping with their disability, and its effectiveness to do so is also proven in some studies.